Perluasan Makna Harta Bersama Perspektif Sosiologi Hukum Islam - Supriatni, Sulistina; Saebani, Beni Ahmad (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This research focuses on the problem of dividing joint assets in divorce which includes the differences in provisions between talak raj'i and talak ba'in, the expansion of types of assets during marriage, and the influence of marriage agreements. In Islamic law, the division of joint property is influenced by the status of the talak, where in talak raj'i, the division is postponed to allow for reconciliation, whereas in talak ba'in, the division is carried out immediately because the divorce is final. In addition, all income or assets obtained during the marriage, including insurance and other funds, are recognized as part of joint assets. The existence of a marriage agreement also plays an important role in accordance with Articles 45, 52 and 97 of the Compilation of Islamic Law, which regulate the division of assets based on an initial agreement. This research shows the importance of a fair and sharia-based legal approach in resolving issues regarding the distribution of joint assets. Abstrak Penelitian ini berfokus pada permasalahan pembagian harta bersama dalam perceraian yang mencakup perbedaan ketentuan antara talak raj’i dan talak ba’in, perluasan jenis aset selama perkawinan, serta pengaruh perjanjian perkawinan. Dalam hukum Islam, pembagian harta bersama yang dipengaruhi oleh status talak, di mana pada talak raj’i, pembagian ditunda untuk memungkinkan rekonsiliasi, sedangkan pada talak ba’in, pembagian dilakukan segera karena perceraian bersifat final. Selain itu, seluruh pendapatan atau aset yang diperoleh selama perkawinan, termasuk asuransi dan dana lainnya, diakui sebagai bagian dari harta bersama. Keberadaan perjanjian perkawinan juga memainkan peran penting sesuai dengan Pasal 45, 52, dan 97 Kompilasi Hukum Islam, yang mengatur pembagian harta berdasarkan kesepakatan awal. Penelitian ini menunjukkan pentingnya pendekatan hukum yang adil dan berbasis syariat dalam menyelesaikan persoalan pembagian harta bersama.